Ответ:
1) y =
2)y =
Объяснение:
1) 2×0+3y-4=0
3y=4
y=
2) 3×2+3y-1=0
6+3y=1
3y=-5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) y =![\frac{4}{3} \frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
2)y =![-\frac{5}{3} -\frac{5}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B3%7D)
Объяснение:
1) 2×0+3y-4=0
3y=4
y=![\frac{4}{3} \frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
2) 3×2+3y-1=0
6+3y=1
3y=-5
y=![-\frac{5}{3} -\frac{5}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B3%7D)